2014
DOI: 10.1007/s12094-014-1160-3
|View full text |Cite
|
Sign up to set email alerts
|

High Sam68 expression predicts poor prognosis in non-small cell lung cancer

Abstract: Our results suggest that high Sam68 expression predicts poor prognosis of NSCLC patients, and Sam68 may be potentially a prognostic biomarker for NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
4
13
0
Order By: Relevance
“…It has been reported that high expression of Sam68 is a is a predictor of poor prognosis in non-small cell lung cancer, oral tongue cancer, early-stage cervical cancer and colorectal cancer (8,9,13,14). In the present study, the expression level of Sam68 was demonstrated to be higher in NB tissues compared with their matched adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been reported that high expression of Sam68 is a is a predictor of poor prognosis in non-small cell lung cancer, oral tongue cancer, early-stage cervical cancer and colorectal cancer (8,9,13,14). In the present study, the expression level of Sam68 was demonstrated to be higher in NB tissues compared with their matched adjacent normal tissues.…”
Section: Discussionsupporting
confidence: 54%
“…Previously, Sam68 was identified to be frequently upregulated in cancer and has an oncogenic role in inflammatory carcinogenesis, tumor invasion and metastasis (8,9). Sam68 is predicated to be a target gene of miR-203, according to bioinformatic analysis, however, whether miR-203 directly mediates the expression of Sam68 and their roles in NB remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with the suggested oncogenic property, Sam68 has also been found to be overexpressed in breast cancer [17,20], prostate cancer [21,27], nonsmall cell lung cancer [24], and neuroblastoma [28]. These studies have suggested that Sam68 is upregulated in many malignant tumor, and its upregulation correlated with shorter survival rates.…”
Section: Discussionsupporting
confidence: 58%
“…Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as an internal loading control. Experiments were performed in triplicate in three independent experiments.Western blotting was conducted according to the standard method as mentioned previously[24], using anti-Sam68 antibody (1:1000 dilution; Santa Cruz). Anti-α-tubulin antibody (1:1000 dilution; Santa Cruz) was used as the loading control.…”
mentioning
confidence: 99%
“…The expression of Sam68 is often elevated in human cancers, including breast, colorectal, esophageal, endometrial, cervical, renal, lung, bladder, ovarian, neural, and prostate cancers [415]. Furthermore, overexpression of Sam68 has been shown to correlate with poor survival prognosis in renal cell carcinoma, colorectal cancer, and non-small cell lung cancer patients [5, 9, 10]. In some cancers, high expression of Sam68 correlates with low expression of certain miRNAs shown to target Sam68, such as in the case of miR-203 and miR-204 observed in neuroblastoma and breast cancer, respectively [13, 16].…”
Section: Introductionmentioning
confidence: 99%